Analysis of porcine bone marrow-derived macrophage cytokine responses to infection with PRRSV-1 strains of differing virulence - Jackson, Ben; Chrun, Tiphany; Childs, Kay; Wanasen, Nanchaya; Frossard, Jean-Pierre; Graham, Simon P.; Seago, Julian (Frontiers in Virology, 2022)
Porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) causes huge economic losses to the European pig industry. PRRSV-1 is divided into 3 subtypes and exhibits considerable antigenic heterogeneity. Due to its high mutation rate, PRRSV-1 is constantly evolving, and highly virulent, particularly subtype 3 strains, are continually emerging. The mechanism(s) underlying PRRSV-1 virulence have not been fully elucidated. In vivo studies have implicated replication kinetics, cell tropism and an enhanced pro-inflammatory cytokine response as potential contributing factors. However, few strains have been directly compared and differences in in vivo study design have hindered comparison, thus limiting our understanding of PRRSV-1 virulence. To address this knowledge gap, we sought to develop a reverse genetics and ex vivo model system, to attempt to identify correlates of PRRSV-1 virulence and attenuation in vitro. Herein we describe the use of primary porcine bone marrow-derived macrophages (BMDM) to investigate the growth kinetics and induced cytokine profiles of the highly virulent SU1-Bel strain, the low virulence 215-06 strain and the attenuated Olot/91 strain. We show that infection of BMDM with virulent PRRSV-1 strains induced higher expression of IL-6 and IL-8 and lower expression of TNF-α when compared with the attenuated strain. In addition, BMDM infected with SU1-Bel secreted significantly more IFN-α than those infected with PRRSV-1 strains of lower virulence. Interestingly, despite inducing less IFN-α than SU1-Bel, Olot/91 induced much higher levels of expression of several interferon-stimulated genes (ISGs), suggesting that Olot/91 may be less able to counteract type I IFN signaling which may contribute to its attenuated phenotype.